2004
DOI: 10.1245/aso.2004.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Frozen Section and Touch Imprint Cytology for Evaluation of Sentinel Lymph Node Metastasis in Breast Cancer

Abstract: The sensitivity of FS was almost equivalent to that of TIC. TIHC had a better sensitivity than FS and TIC, but it upstaged a few node-negative patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 12 publications
1
26
0
2
Order By: Relevance
“…Touch imprint cytology (TIC), frozen section (FS) analysis and onestep nucleic-acid amplification (OSNA) represent the most common techniques available to intraoperatively detect breast cancer axillary sentinel lymph node (SLN) metastasis [8,9]. However, recent studies have stated that TIC is not anymore, a useful technique to detect SLN metastasis in breast cancer [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Touch imprint cytology (TIC), frozen section (FS) analysis and onestep nucleic-acid amplification (OSNA) represent the most common techniques available to intraoperatively detect breast cancer axillary sentinel lymph node (SLN) metastasis [8,9]. However, recent studies have stated that TIC is not anymore, a useful technique to detect SLN metastasis in breast cancer [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…The most common ones include frozen section (FS), touch imprint cytology (TIC) [8] and one-step nucleicacid amplification (OSNA) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, one might argue that our nomograms are not applicable for institutions, where frozen section is used instead of TIC. However, studies directly comparing frozen section with TIC showed that sensitivities of both methods are comparable [20,21]. Furthermore, Lambert LA et al who validated MSKCC nomogram (which uses frozen section), showed that TIC seems to be an acceptable substitute for frozen section as a nomogram variable [22].…”
Section: Discussionmentioning
confidence: 99%
“…And, last, which is the most limiting step in clinical practice, neither imprint cytology nor frozen sections yield satisfactory results as they do for breast cancer and melanoma [5,11,12]. In breast cancer and melanoma, many centers report that intraoperative diagnosis with these methods shows high sensitivity and high specificity, both being higher than 90% for each method [6,13].…”
Section: Discussionmentioning
confidence: 99%